Study on Fulfilling Needs and Availability of Clean Water in Manado City in 2045 - Mananoma, Tiny; Ratu, Yosua Aditya; Moningka, Frederiko Marchiano Imanuel (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2025)
Clean water is an essential element for human life. The need for water continues to increase along with population growth. Rivers are a good source of clean water. Understanding water availability in the river that we will use as a clean water source is very important. In 2022, Manado City will have a population of 454,606 people. This study aims to determine the water demand in Manado City in 2045 and whether the Tondano River will be able to meet the water demand by 2045. This research uses a quantitative method, where the data used includes Tondano River discharge data processed using the analysis of water resource availability and Manado City population data using exponential regression analysis. In 2045, the population is projected to reach 549,438 people. Water demand is calculated based on the domestic, non-domestic, and water loss sectors. The total water demand in 2045 was 1,860.08 liters per day. If the total water demand is added to the peak hour factor, the total water demand becomes 5,533.28 liters, while the mainstay discharge of the Tondano River for Q95 is 4,511.34 liters per day. It can be seen that in 2045, the Tondano River can still meet the clean water needs of the Manado community. However, if the peak hour factor for Q95 is added, the Tondano River cannot meet the clean water needs of the Manado people.